The Integration of 2013 Curriculum with Pesantren Curriculum in Fiqh Subject of Class X at Madrasah Aliyah Al-Mawaddah Ponorogo - Nurcendani, Riska Wahyu; Ratnasari, Dwi (Jurnal Pendidikan Agama Islam, 2020)
The aims of this research are to discover the implementation, supporting factors, and inhibiting factors of the integration of the 2013 curriculum with the pesantren curriculum in fiqh subject of class X at Madrasah Aliyah Al-Mawaddah Ponorogo. This research is a field research. The techniques of data collection used were interview, observation, and documentation. The process of analyzing the data of this study used data collection, data reduction, data presentation, and drawing data conclusions. The validity of the data was tested by triagulation technique. The research results show that: (1) The application of the integration of the 2013 curriculum with the KMI curriculum in the subject of fiqh class X Madrasah Aliyah Al-Mawaddah was held by setting the hours of study for one semester to study the KMI fiqh material and repeating the 2013 curriculum (Ministry of Religion Curriculum) fiqh material. (2) Supporting factors are the support of the pesantren leader in form of policies, a similarity in specifications between the subject matter of the 2013 curriculum curriculum (Ministry of Religion) and the KMI curriculum, and the habits of students using Arabic as the language instruction. The inhibiting factors are limited study time and crowded pesantren activities.